WASTE BANK MANAGEMENT AND COMMUNITY PERCEPTIONS ABOUT BAROKAH BERSAMA WASTE BANK AT JAMBI - Erris, Erris; Krisdiyanta, Krisdiyanta (Yayasan Education and Social Center, 2022)
Community involvement in joining in the management of the Waste Bank aims to make people from the household level able to manage their household waste, namely reducing waste from waste sources, so that it can be a good solution in waste management and with 3R efforts on the community which is expected to reduce the burden of waste accumulation—at the TPS, extending the life of the TPA, as well as providing additional income for people who save their waste through a waste bank. It can change the community's paradigm in viewing waste from initially viewing waste as useless waste to being a resource with economic value. The type of research conducted is descriptive research with the main objective of knowing the perceptions of homemakers about the management of the Barokah Bersama Waste Bank in Jambi City and waste management at the Barokah Bersama Waste Bank in Jambi City. Which has been observed to determine the required management standards Regulation of the State Minister of the Environment of the Republic of Indonesia Number 13 of 2012 concerning the guidelines for implementing Reduce, Reuse, and Recycle through Waste Banks. It is known that of the three standard requirements for the management of Waste Banks that have been implemented properly, only a few have been implemented. have not met the requirements, namely the lack of customers receiving counselling from the Government and the Barokah Waste Bank, the number of daily managers of the Barokah Bersama Waste Bank is only three people. In contrast, at least 5 (five) people under the Management Standard n Waste Banks requirements, the number of waste savers that do not increase on average is 5-10 savers every month. There is no replication of local Waste Banks to other areas